Bottom-Up Innovative Responses to Covid-19 in Latin America and the Caribbean: Addressing Deprioritized Populations; [Respostas Inovadoras de Baixo Para Cima À Covid-19 Na América Latina E No Caribe Com Foco Em Populações Não Priorizadas]; [Respuestas Innovadoras a la Covid-19 Generadas Desde la Base en América Latina y el Caribe: Abordaje de Grupos Poblacionales Desatendidos] - Maddaleno-Herrera, M; Villalobos-Dintrans, P; Castillo-Arellano, C (Pan American Health Organization, 2023)
Objective. To identify and describe innovative initiatives implemented as a response to the interruption of health services during the COVID-19 pandemic in Latin America and the Caribbean (LAC). Methods. This was a descriptive study that reviewed 34 initiatives implemented during the COVID-19 pandemic in LAC to address health services needs among deprioritized groups. The review of initiatives included four phases: a call for submissions of innovative initiatives from LAC countries; a selection of initiatives that had the ability to address health services gaps and that were innovative and effective; systematization and cataloging of the selected initiatives; and a content analysis of the information collected. Data were analyzed from September to October 2021. Results. The 34 initiatives show important variations regarding the target populations, the stakeholders involved, level of implementation, strategies, scope, and relevance of the innovative initiative. There was also evidence of the emergence of a bottom-up set of actions in the absence of top-down actions. Conclusion. The findings of this descriptive review of 34 initiatives implemented during the COVID-19 pandemic in LAC suggest that systematizing the strategies and lessons learned has the potential to expand learning for re-establishing and improving post-pandemic health services. © 2023 Pan American Health Organization. All rights reserved.